"Without Conquest or Purchase": The Annexation Moment in British Columbia, 1866-1871 - Holloway, Brent (Université d'Ottawa / University of Ottawa, 2016)
While the annexation movement in British Columbia appears to have been short-lived and disorganized, it was nevertheless understood as a serious threat to British rule. This study seeks to reconcile this contradiction through an examination of newspapers, debates, despatches, and correspondence drawn from British Columbia, Britain, Canada, and the United States. In examining the movement, this study reveals both the peculiar capacity of the minor agitation to present an exaggerated image of its popularity, and the key geopolitical assumptions which led observers to overestimate its importance. As the narrative spectre of annexationism outpaced the actual strength of the movement, confederationist leaders and British and American authorities were led to embark on misguided political strategies. The British Columbian annexation movement’s disproportionate impact reveals the complex interaction between local politics and global forces in British North American history, and demonstrates the role of ideology and rumour-making in shaping global political narratives.
Keywords: British Columbia; British North America; Great Britain; United States; Annexation; Confederation